2020
DOI: 10.1002/apj.2535
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxymethylation of xylenol over micro/mesoporous TiO2‐containing bifunctional catalyst: Effect of the Y zeolite incorporation with MCM‐41

Abstract: The hydrodemethylation reaction of 3,4-xylenol on micro/mesoporous catalysts with active component TiO 2 was studied. TiO 2 /YM-m and TiO 2 /YM-c micro/mesoporous materials were, respectively, derived by loading TiO 2 with the composition and mechanical mixing of Al-MCM-41 and HY zeolite. The effect of the bifunctional catalysts on the catalytic performance of hydroxymethylation of xylenol before and after the introduction of Al-MCM-41 into HY was investigated in this study. Compared with TiO 2 /Y catalyst, Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…32,33 In the preparation stage, the mesoporous MOR or nano MOR were synthesized to shorten the diffusion path and overcome the diffusion resistance. 34,35 By employing the seed technique and an organosilane surfactant to generate the mesopores in the MOR, Kim et al 36 prepared MOR that resembled nanorods. It is reported that hexadecyltrimethylammonium bromide (CTAB) can regulate the morphology of molecular sieve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 In the preparation stage, the mesoporous MOR or nano MOR were synthesized to shorten the diffusion path and overcome the diffusion resistance. 34,35 By employing the seed technique and an organosilane surfactant to generate the mesopores in the MOR, Kim et al 36 prepared MOR that resembled nanorods. It is reported that hexadecyltrimethylammonium bromide (CTAB) can regulate the morphology of molecular sieve.…”
Section: Introductionmentioning
confidence: 99%
“…Post‐treatments include methods such as selective dealumination, 25–27 metal modification, 28–31 and pyridine adsorption 32,33 . In the preparation stage, the mesoporous MOR or nano MOR were synthesized to shorten the diffusion path and overcome the diffusion resistance 34,35 . By employing the seed technique and an organosilane surfactant to generate the mesopores in the MOR, Kim et al 36 prepared MOR that resembled nanorods.…”
Section: Introductionmentioning
confidence: 99%